2018
DOI: 10.7717/peerj.5991
|View full text |Cite
|
Sign up to set email alerts
|

Chemical analysis and evaluation of antioxidant and antimicrobial activities of fruit fractions ofMauritia flexuosaL. f. (Arecaceae)

Abstract: BackgroundFruit consumption is currently considered beyond the nutritional aspects because of the important roles in disease prevention and benefits to health. The objective of this study was to characterize the chemical profile and evaluate the antioxidant and antimicrobial properties of different fractions obtained from fruit pulps of Mauritia flexuosa (MFFs).MethodsInitially, chloroform, ethyl acetate and ethanol fractions were obtained from the pulps. Quantifications of total phenols and flavonoids were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 59 publications
1
15
0
4
Order By: Relevance
“…They are further classified into blocking agents and suppressing agents depending on their ability to prevent carcinogenesis and suppress neoplastic cell growth respectively [42]. Based on the properties reported for phenolic compounds [43,44] and the results presented in this study, we propose that 2,4,6-THBA can act as both—a blocking and a suppressing agent. Since it is a phenolic compound with multiple hydroxyl groups, it can act as a blocking agent and exert its effect through its anti-oxidant properties [45].…”
Section: Discussionmentioning
confidence: 81%
“…They are further classified into blocking agents and suppressing agents depending on their ability to prevent carcinogenesis and suppress neoplastic cell growth respectively [42]. Based on the properties reported for phenolic compounds [43,44] and the results presented in this study, we propose that 2,4,6-THBA can act as both—a blocking and a suppressing agent. Since it is a phenolic compound with multiple hydroxyl groups, it can act as a blocking agent and exert its effect through its anti-oxidant properties [45].…”
Section: Discussionmentioning
confidence: 81%
“…In our study, the samples were obtained from the same biome (Amazon region). Nonato et al. (2018) also carried out a chemical analysis and evaluation of in vitro antioxidant capacity using different fractions (chloroform, ethyl acetate and ethanol) obtained from the pulp of Mauritia flexuosa L.f. using a Soxhlet extractor.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the samples were obtained from the same biome (Amazon region). Nonato et al (2018) also carried out a chemical analysis and evaluation of in vitro antioxidant capacity using different fractions (chloroform, ethyl acetate and ethanol) obtained from the pulp of Mauritia flexuosa L.f. using a Soxhlet extractor. A higher content of phenolic and flavonoid compounds was observed in the ethyl acetate and ethanolic fractions (26.84 and 22.69 μg GAE/g, and 11.82 and 12.47 μg EQE/g; respectively); however, these values were much lower than the ones reported in our research because in the previous study only the lipid fraction of the samples was evaluated.…”
Section: Total Phenolics Flavonoids and Carotenoids And Dpph Radical Scavenging Activitymentioning
confidence: 99%
“…Souza et al [12] identified the phenolic compounds cyanidin 3-O-rutinoside, chlorogenic acid, and rutin in Oenocarpus distichus fruits, using high-performance liquid chromatography (HPLC). It has been reported the presence of catechin, caffeic acid, rutin, orientin, quercetin, apigenin, luteolin, and kaempferol in Mauritia flexuosa L. f. (Arecaceae), another fruit from Amazonian biome [13].…”
Section: Introductionmentioning
confidence: 99%